Evaluating the Effects of Popular Music on Cardiopulmonary Resuscitation Training in Nursing Students: A Randomized Controlled Study - Gülten Sucu Dağ; Sevinç Taştan; Başak Bayram; Neşe Çolak (Mediterranean Nursing and Midwifery)
Objective: This study aimed to analyze the short- and long-term effects of musical memory created using a national popular song on achieving the recommended compression rate, depth, and compression-breath rate for nursing students who received cardiopulmonary resuscitation (CPR) training. Method: This study had an experimental, randomized post-test control group design. The study was conducted between February and June 2018 on 49 third-year nursing students who received CPR training for the first time. The control group received standard CPR training, whereas the intervention group received CPR training using a nationally popular song. The study evaluated compression rate and depth, satisfaction with CPR training, and arm pain during CPR. Data were collected immediately after CPR training (short-term) and six weeks after training (long-term). Results: The differences between the control and intervention groups regarding the correct and incorrect breath rates were not statistically significant (p>0.05). In addition, there was no significant difference between the control and intervention groups in terms of compression and breathing rates measured six weeks after CPR training was not statistically (p>0.05). Satisfaction with CPR training was higher in the control group. Conclusion: Although existing studies suggested that popular music is an effective tool for achieving the recommended compression rate, this study did not find any significant impact of popular national music on chest compression performance.